1996
DOI: 10.1183/09031936.96.09020207
|View full text |Cite
|
Sign up to set email alerts
|

Association between toluene diisocyanate-induced asthma and DQB1 markers: a possible role for aspartic acid at position 57

Abstract: Toluene diisocyanate (TDI) is the most common cause of occupational asthma in western countries. The aim of this study was to investigate whether genetic factors are involved in toluene diisocyanate-induced asthma.We studied the frequency of human leucocyte antigen (HLA) class II genetic markers in three groups of subjects: 1) subjects with TDI-induced asthma (n=30); 2) exposed subjects with no history of TDI-induced asthma (n=12); and 3) normal subjects not exposed to TDI (n=126). Venous blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 21 publications
(26 reference statements)
5
42
0
1
Order By: Relevance
“…In workers with exposure to diisocyanates, HLA-DQB1*0503 and DQB1*0201/0301 alleles are associated with asthma, whereas HLA-DQB1*O501 and DQA1*0101-DQB1*0501-DR1 appear to be protective (29). The alleles, HLA-DQB1*0503 and HLA-DQB1*0501, differ at residue 57 for a single amino acid, aspartic acid in DQB1*0503 and valine in DQB1*0501, suggesting that residue 57 may be a potentially critical location in the development of asthma (30). Associations with MHC proteins have also been described in acid anhydride-induced asthma (31), in platinum salts-induced asthma, and in red cedar-induced asthma (32).…”
Section: Pathogenesis/mechanismsmentioning
confidence: 99%
“…In workers with exposure to diisocyanates, HLA-DQB1*0503 and DQB1*0201/0301 alleles are associated with asthma, whereas HLA-DQB1*O501 and DQA1*0101-DQB1*0501-DR1 appear to be protective (29). The alleles, HLA-DQB1*0503 and HLA-DQB1*0501, differ at residue 57 for a single amino acid, aspartic acid in DQB1*0503 and valine in DQB1*0501, suggesting that residue 57 may be a potentially critical location in the development of asthma (30). Associations with MHC proteins have also been described in acid anhydride-induced asthma (31), in platinum salts-induced asthma, and in red cedar-induced asthma (32).…”
Section: Pathogenesis/mechanismsmentioning
confidence: 99%
“…Although it is well known that mastocytosis can lead to the development of non-IgE-mediated severe intraoperative reactions, without standard guidelines for the intraoperative management of these patients, premedication consisted of antihistamines, corticosteroids, and disodium cromoglycate by means of nebulization and the oral route; stress-reducing ansiolitics were administered, and safer anesthetic drugs were used. 7,8 No undesired intraoperative or postoperative reactions occurred.…”
Section: Mast Cell Diseases and The Severity And Course Of Intraoperamentioning
confidence: 93%
“…3 For TDI-OA, the pathogenic mechanism is unknown, and there have been several reports on the genetic susceptibility of Italian 4,5,7 and Korean 6 populations.…”
mentioning
confidence: 99%
“…Bernstein et al 50) reported evidence that the involvement of the TCR Vβ repertoire expression increased the expression Vβ1 and Vβ5 after in vitro stimulation in patients who were exposed to diisocyanate. Bignon et al 51) , Balboni et al 52) and Mapp et al 53) studied the HLA class II alleles' contribution to susceptibility or resistance to isocyanate-induced asthma in exposed workers. They reported that allele DQB1*0503 and the allele combination DQB1*0201/0301 were associated with susceptibility to the disease.…”
Section: Immunological Mechanisms and Clinical Responsesmentioning
confidence: 99%